Indeks Masa Tubuh (IMT) Berhubungan dengan Angka Kejadian Anemia Ibu Hamil - Apriliana Andin; Andri Nur Sholihah (Midwifery Care Journal, 2026)
Pregnancy anemia is a pathological state defined by elevated plasma fluid volumes during gestation, leading to hemodilution and a hemoglobin concentration falling below 11 grams. The nutritional status of the mother is paramount for both maternal and fetal health, which is often assessed through Body Mass Index (BMI). Indonesia has been documented as the nation with the highest incidence of anemia, with data from basic health research indicating that the prevalence of anemia among pregnant women reached 48.9% in 2018. The incidence of anemia in pregnant women, particularly in Yogyakarta, showed an increase to 16.5% in 2021. This research seeks to elucidate the correlation between Body Mass Index and the frequency of anemia cases among pregnant women at the Community Health Center Sleman. The study employs a correlational analytical method with a retrospective design. The target population for this investigation comprised pregnant women in their second and third trimesters who underwent pregnancy assessments between November 2022 and October 2023, totaling 348 participants. The sampling strategy implemented was probability sampling, specifically random sampling with proportional allocation, resulting in 80 respondents, with the data analyzed via chi-square statistical methods. The findings of this study yielded a p-value of 0.000, indicating a statistically significant association between Body Mass Index (BMI) and the incidence of anemia among pregnant women at Puskesmas Sleman. It is recommended that pregnant women engage in a minimum of four prenatal consultations and prioritize their nutritional intake to mitigate the risk of anemia